Project Environmental change supports ecological transition in geography - Vovk, Ana; Davidovič, Danijel (Journal for Geography, 2022)
Project Environmental change supports ecological transition in geography The article combines the main points of the European Green Deal and digitalization of Europe, which emphasize the importance of a sustainable way of life on Earth and the role of the individual in the realization of sustainability. To achieve these goals, the EU financially supports a number of projects with the goal to develop learning tools (modules, applications) for many target groups through a formal and informal approach. As an example, we present the Environmental Change project at the Faculty of Arts in Maribor, which offers six environmentally oriented modules, primarily intended for educators and small and medium-sized companies in order to upgrade sustainable practices. The interdisciplinary orientation of geography is highlighted, which would enhance the importance of geographical science in society by including additional sustainable approaches.